2017
DOI: 10.1039/c7tc02302b
|View full text |Cite
|
Sign up to set email alerts
|

Band bending in conjugated polymer films: role of morphology and implications for bulk charge transport characteristics

Abstract: The band bending effect depends on the morphology of the conjugated polymer as studied by Kelvin probe force microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…These flat bands they attributed to the high purity of the used TPD. Band bending for nominally pristine organic semiconductors has also been observed, when studying various interfaces with conjugated polymers [160][161][162][163][164][165] and when separating the metal from the organic semiconductor using an insulating alkalihalide layer. [166] In such cases, this is typically explained by the filling of electronic states in molecules at some distance from the interface.…”
Section: Organic Monolayers Versus Multilayers and Doped Filmsmentioning
confidence: 90%
“…These flat bands they attributed to the high purity of the used TPD. Band bending for nominally pristine organic semiconductors has also been observed, when studying various interfaces with conjugated polymers [160][161][162][163][164][165] and when separating the metal from the organic semiconductor using an insulating alkalihalide layer. [166] In such cases, this is typically explained by the filling of electronic states in molecules at some distance from the interface.…”
Section: Organic Monolayers Versus Multilayers and Doped Filmsmentioning
confidence: 90%
“…It has been shown that for conductive organic semiconductors, only the free charge carriers responsible for effective charge carrier mobility actually contribute to the formation of space charge layers, which results in band bending at an interface. 59 For such polymers, it has also been shown that band bending on the surface actually depends on the film thickness. Thus, at low concentrations of mobile charge carriers, which is considered the default situation in the majority of polymer photocatalysts, the formation of a space charge layer with significant extension is questionable.…”
Section: <Figure 2>mentioning
confidence: 99%
“…MAPLE has successfully been used to grow thin conjugated polymer films for various organic electronic applications . Our prior research has begun to elucidate fundamental connections between crystallization, morphology, electronic structure, and carrier transport in MAPLE‐deposited conjugated polymer films . An important, yet poorly understood problem is understanding the role of molecular weight on the structure and physical properties of conjugated polymers deposited by the MAPLE technique.…”
Section: Introductionmentioning
confidence: 99%